To factor the equation, first make sure the right hand side is equal to 0. Do this by subtracting 25 from both sides of the equation.
The equation becomes,
n^2-8n-9 = 0
Factoring the equation now gives you (n-9)(n+1) = 0.
In order to find the solutions to this equation, find values of 'n' that make the equation equal to 0.
In this case, if n is 9 or -1, we get the answer 0.
Proof: (9-9)(n+1) => (0)(n+1) = 0
or (n-9)(-1+1) => (n-9)(0) = 0.
Hope this made sense! If it didn't, please ask questions!